Vibrio Dynamics and Health Status of Pacific White Shrimp Fed with Cinnamaldehyde-Containing Feed - Dian Eka Ramadhani; Andri Hendriana; Dinamella Wahjuningrum; Muhammad Arif Mulya (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight Research Cinnamaldehyde for shrimp Dynamics of Vibrio and the correlation with shrimp health status Green and yellow Vibrio bacteria in water, intestine, and hepatopancreas of shrimp Cinnamaldehyde decrease the number of green Vibrio bacteria Abstract Disease can cause shrimp mortality and high economic losses caused by Vibriosis group. One alternative is using cinnamaldehyde which function as an anti-microbial and inhibit the production of toxins released by microorganisms. This study aimed to evaluate the administration of cinnamaldehyde on the dynamics of Vibrio bacteria and the health status of Pacific white shrimp fed with cinnamaldehyde-containing feed. This study used a completely randomized design (CRD) consisted of 4 treatments and 3 replications consisting of treatment K, A, B, and C which mean feeding without cinnamaldehyde, feeding containing cinnamaldehyde dose of 0.05%, 0.1%, and 0.2% respectively. Parameters included total bacteria (green and yellow Vibrio) in water, intestine, and hepatopancreas, as well as immune responses parameters, including total hemocyte count (THC), respiratory burst (RB), and phenol-oxidase (PO). All data were tabulated in Microsoft Excel 2016 and all statistical analysis was conducted in the SPSS v.22.0 software with one-way ANOVA followed by Duncan Multiple Range Test (DMRT (P=0.05). The results showed that the administration of cinnamaldehyde influences the dynamics of Vibrio and health status of shrimp. At the beginning and at the end of cinnamaldehyde administration, green and yellow Vibrio bacteria are mostly found in water, intestine, and hepatopancreas. The administration of cinnamaldehyde to Pacific white shrimp can reduce the number of green Vibrio bacteria both in the intestine and hepatopancreas as shown in treatments C and B. Cinnamaldehyde also affected the higher percentage of yellow Vibrio bacteria in treatments C and B compared to control (K). The highest immune responses of THC and RB were produced in treatments A and C compared to K. The decrease of green Vibrio bacteria and increased colonization of yellow Vibrio bacteria were correlated with immune responses. The best treatment in this study is treatment C.